Short Communication First Record of the Polychaete Worm Ceratonereis (Composetia) burmensis (Phyllodocida: Nereididae) from Pakistan: Short Communication: First Record of the Polychaeta Worm - Aslam, Sadar; Mustaquim, Javed; Siddiqui, Ghazala (Biological Sciences - PJSIR, 2020)
Ceratonereis (Composetia) burmensis Monro (1937) is reported for the first time from Pakistan. A single specimen was collected from Hab river delta (24°53’13.45’’ N and 66°42’18.04’’ E) on the Balochistan coast in September, 2017. Two species of Ceratonereis previously reported from Pakistan are: Ceratonereis marmorata (Horst, 1924) and Ceratonereis sp. (Cpmposetia) burmensis differs from C. marmorata in having a prostomium that is not marmorated. It also differs from Ceratonereis sp. in having neuropodial falcigers. C. (Composetia) burmensis has wide distribution from Iran to China.